Exposure and risk assessment of urinary trans, trans-Muconic acid in school-age children in the vicinity of a petrochemical complex in Central Taiwan - Cheng, Po-Keng; Ponnusamy, Vinoth Kumar; Prakasham, Karthikeyan; Huang, Hsin-I; Chang, Wan-Ting; Huang, Po-Chin (Frontiers in Public Health, 2023)
School-age children living near large petrochemical factories may be at high risk of exposure to benzene released during manufacturing processes. We aimed to investigate the urinary concentrations of trans, trans-muconic acid (t,t-MA) in school-age children living near a petrochemical complex and to estimate their cumulative risk of benzene exposure. We examined an established cohort (Taiwan Petrochemical Complex Cohort for Children, TPE3C) of school-age children (aged 6–13 years) who lived near large petrochemical factories in central Taiwan between October 2013 and September 2014. The cohort comprised 297 children from five elementary schools, namely S.-C. Branch (n = 63, school A, ~0.9 km), F.-A. (n = 51, school B, ~2.7 km), C.-T. (n = 63, school C, ~5.5 km), M.-L. (n = 54, school D, ~6.9 km), and L.-F. (n = 66, school E, ~8.6 km). We analyzed the urinary t,t-MA levels of each participant and estimated their daily intake of benzene. We also performed multiple regression analysis to investigate potential risk factors for a high urinary t,t-MA level in the study cohort. The median urinary t,t-MA levels and median estimated benzene daily intake of the children from each school were as follows: school A, 64.07 ng/mL, 11.13 μg/kg/day; school B, 61.01 ng/mL, 15.32 μg/kg/day; school C, 59.38 ng/mL, 14.81 μg/kg/day; school D, 42.35 ng/mL, 11.67 μg/kg/day; school E, undetected, 0.14 μg/kg/day. The distance between a school and a petrochemical complex (greater distance: β = −0.26, 95% confidence interval [CI] = −0.52 to 0.00, p = 0.053), and the age of the children (older age: β = −3.44, 95% CI = −5.90 to −1.46, p < 0.001) were identified as potential risk factors. After confounders were adjusted for, the creatinine adjusted urinary t,t-MA levels of the school-age children tended to be lower when the distance between their school and a petrochemical complex was greater.